PENGARUH PERJANJIAN KERJA WAKTU TERTENTU (PKWT) TERHADAP KINERJA KARYAWAN MELALUI KOMPENSASI SEBAGAI VARIABEL MEDIASI PADA PT XYZ - Shela Wardani, Neriza Herdina; Cahyadi, Nur (MANAJEMEN DEWANTARA, 2024)
This research uses compensation as a mediating variable to find out how a Specific Time Work Agreement (PKWT) affects worker performance. Likert scales and quantitative descriptive techniques were used to collect data for research at PT XYZ. There were 110 PKWT employees selected for this research using a purposive sampling technique. The research findings indicate that the Specific Time Work Agreement (PKWT) significantly affects compensation, demonstrating a notably high influence value of 0. 872. This evidence underscores that a transparent and equitable implementation of PKWT can enhance employee trust and satisfaction regarding their compensation. Moreover, the study provides empirical support for the notion that a well-structured fixed-term work agreement, coupled with fair compensation, serves as an essential strategy for boosting employee performance. A work environment that values employee rights and contributions fosters high motivation, ultimately leading to improved productivity and enhanced overall work quality.